Clean milk production practices and its impact on the prevention and control of mastitis in Tiruchirapalli district of Tamil Nadu - G, RAJARAJAN (Indian Journal of Dairy Science, 2020)
Mastitis is one of the major infectious diseases affecting dairy cows and causing economic loss. Majority of the rural dairy farmers are not aware of preventing mastitis through management practices. Lack of adoption of clean milk production practices is the major reason for mastitis. So the focus of study was imparting knowledge on clean milk production practices to dairy farmers from selected villages in Tiruchirapalli district along with management of mastitis in dairy animals through capacity building programme.Â After the adoption of clean milk production practices, there was remarkable reduction in the incidence of mastitis from 19.33 per cent to 2.4 per cent. The keeping quality of milk was also improved by enhancement in methylene blue dye reduction time (MBRT). This was an indirect indication of improved microbial quality of raw milk. The subclinical mastitis was monitored with somatic cell count (SCC) and the quarters of udder health by California mastitis test (CMT) respectively. The mastitic animal was treated effectively with suitable antibiotic by conducting antibiotic sensitivity test (ABST) and thereby protected the dairy farmers from huge economic loss. Â